STUDIES ON THE DISTRIBUTION IN TIME AND SPACE OF THE PERIPHYTON OF SOME PERENNIAL PONDS OF NALANDA (BIHAR) - KUMAR, PRAMOD (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2009)
On the basis of observation made on distribution of Periphyton of some perennial ponds of Nalanda it is clear that periphytons are having considerable significance as feeding demand of some fishes and other aquatic organisation. The latest definition usually referred to the assemblage of organisms attached to any substratum so being such type of organisms. These periphyton are significant for pisciculture and balancing Biotic community. The species diversity and evenness value have also been estimated in this research work to gain the understanding of the structure of periphyton Community and an attempt has been made also to know the periodicity in periphytic abundance.